The obstetric syndromes: clinical relevance of placental hormones. Issue 2 (March 2013) - Severi, Filiberto Maria; De Bonis, Maria; Vellucci, Francesca Letizia; Voltolini, Chiara; Bocchi, Caterina; Di Tommaso, Mariarosaria; Torricelli, Michela; Petraglia, Felice
Preterm delivery, preeclampsia and intrauterine growth restriction are the major diseases of pregnancy. A key role in their pathogenesis is played by the placenta, which is the source of hormones and other important regulatory molecules providing the metabolic and endocrine homeostasis of the fetal–placental unit. Since obstetric syndromes are characterized by important maternal and neonatal morbidity and mortality worldwide, numerous efforts have been made over the years to prevent and treat them. Due to their complex pathogenesis, however, the therapy is poor and not very effective. Therefore, great emphasis is currently given to the prevention of these diseases through the identification of biochemical and biophysical markers, among which placental factors play a crucial role. The increasing knowledge of the role of placental molecules can indeed lead to the development of new therapeutic and diagnostic tools.